Novel WFS1 variants are associated with different diabetes phenotypes - Wu, Lei; Zhang, Juan; Li, Danjie; Zhang, Zhongyun; Ni, Qicheng; Han, Rulai; Ye, Lei; Zhang, Yifei; Hong, Jie; Wang, Weiqing; Ning, Guang; Gu, Weiqiong (Frontiers in Genetics, 2024)
Background: The WFS1 gene encodes the protein wolframin, which is crucial for maintaining endoplasmic reticulum homeostasis. Variants in this gene are predominantly associated with Wolfram syndrome and have been implicated in other disorders such as diabetes mellitus and psychiatric diseases, which increases the rate of clinical misdiagnosis. Methods: Patients were diagnosed with early-onset unclassified diabetes according to their clinical and laboratory data. We performed whole-exome sequencing (WES) in 165 patients, interpreting variants according to the American College of Medical Genetics/Association for Molecular Pathology (ACMG/AMP) 2015 guidelines. Variant verification was done by Sanger sequencing. In vitro experiments were conducted to evaluate the effects of WFS1 compound heterozygous variants. Results: We identified WFS1 compound heterozygous variants (p.A214fs*74/p.F329I and p.I427S/p.I304T) in two patients with Wolfram Syndrome-Like disorders (WSLD). Both WFS1 compound heterozygous variants were associated with increased ER stress, reduced cell viability, and decreased SERCA2b mRNA levels. Additionally, pathogenic or likely pathogenic WFS1 heterozygous variants were identified in the other three patients. Conclusion: Our results underscore the importance of early genetic testing for diagnosing young-onset diabetes and highlight the clinical relevance of WFS1 variants in increasing ER stress and reducing cell viability. Incorporating these genetic insights into clinical practice can reduce misdiagnoses and improve treatment strategies for related disorders.